Measuring maternal health: focus on maternal morbidity - Firoz, Tabassum; Chou, Doris; von Dadelszen, Peter; Agrawal, Priya; Vanderkruik, Rachel; Tunçalp, Ozge; Magee, Laura A; van Den Broek, Nynke; Say, Lale (Bulletin of the World Health Organization, 2013)
A reduction in maternal mortality has traditionally been used as a critical measure of progress in improving maternal health. If a 75% reduction in maternal mortality between 1990 and 2015 -- the target set under Millennium Development Goal 5 -- is to be attained, people must redouble their efforts. In this endeavour, governments, policy-makers, donors, researchers, civil society and other stakeholders have come together in unprecedented fashion. Yet despite the fact that the maternal mortality ratio is considered one of the main indicators of a country's status in the area of maternal health, the burden of maternal mortality is only a small fraction of the burden of maternal morbidity -- the health problems borne by women during pregnancy and the postpartum period. The true burden of maternal morbidity is still not known, however. Existing estimates and calculations are not based on standard, well documented and transparent methods. Such methods are not very useful and have poor validity for informing efforts to address the problem of maternal morbidity.